2019
DOI: 10.4236/jcc.2019.712011
|View full text |Cite
|
Sign up to set email alerts
|

System Implementation Failures in the ERP Development Process

Abstract: ERP mainly relates to business management software which consists of several modules that are important for the growth and survival of different types of businesses and organisations. The integration of related business applications in an organisation can bring significant advantages to the business by enabling faster supply chain management. ERP implementation enables firms to adapt and configure information flows and integrate business processes in order to enhance business performance. System implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Poor knowledge transfer, users' resistance to change, ERP system misfit with organizational culture & structure, unrealistic expectations from top management concerning the ERP, inaccurate data, lack of appropriate culture, internal conflict between departments, poor testing, lack of organizational readiness, poor quality of testing, lack of senior management leadership, too tight project schedule, inadequate resources, conflict between organization & consultant, lack of vendor support, high system complexity, inadequate ERP teamwork and composition, poor consultant effectiveness, unclear concept of the nature & use of ERP system from the users' perspective, functionality problems with the system, conflict between organization & vendor, high turnover rate of project team members, software modification, key users' Table 6. Continued replacements after their training, wrong ERP product selection, and weak commitment of project team are some of the less serious but still significant challenges that influence ERP implementation (Abdelaziz et al, 2019;Amid et al, 2012;Arachchi et al, 2019;Aranyossy et al, 2018;Basu & Biswas, 2013;Bingi et al, 2006;Chakravorty et al, 2016;Chen et al, 2009;Garg & Khurana, 2017;Jharkharia, 2011;Kheybari et al, 2020;Kholeif et al, 2007;Kohansal, 2019;Mahmood et al, 2019;Menon et al, 2019;Narayanamurthy & Gurumurthy, 2017;Noudoostbeni et al, 2009;Pan et al, 2008;Peci & Važan, 2014;Ravasan & Mansouri, 2014;Saadé et al, 2017;Sodhi et al, 2019;Virzi, 2019;Wong et al, 2005). It was discovered in previous research that the highly ranked ERP implementation challenges identified through a review of the literature also occurred as highly ranked challenges in similar studies.…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Poor knowledge transfer, users' resistance to change, ERP system misfit with organizational culture & structure, unrealistic expectations from top management concerning the ERP, inaccurate data, lack of appropriate culture, internal conflict between departments, poor testing, lack of organizational readiness, poor quality of testing, lack of senior management leadership, too tight project schedule, inadequate resources, conflict between organization & consultant, lack of vendor support, high system complexity, inadequate ERP teamwork and composition, poor consultant effectiveness, unclear concept of the nature & use of ERP system from the users' perspective, functionality problems with the system, conflict between organization & vendor, high turnover rate of project team members, software modification, key users' Table 6. Continued replacements after their training, wrong ERP product selection, and weak commitment of project team are some of the less serious but still significant challenges that influence ERP implementation (Abdelaziz et al, 2019;Amid et al, 2012;Arachchi et al, 2019;Aranyossy et al, 2018;Basu & Biswas, 2013;Bingi et al, 2006;Chakravorty et al, 2016;Chen et al, 2009;Garg & Khurana, 2017;Jharkharia, 2011;Kheybari et al, 2020;Kholeif et al, 2007;Kohansal, 2019;Mahmood et al, 2019;Menon et al, 2019;Narayanamurthy & Gurumurthy, 2017;Noudoostbeni et al, 2009;Pan et al, 2008;Peci & Važan, 2014;Ravasan & Mansouri, 2014;Saadé et al, 2017;Sodhi et al, 2019;Virzi, 2019;Wong et al, 2005). It was discovered in previous research that the highly ranked ERP implementation challenges identified through a review of the literature also occurred as highly ranked challenges in similar studies.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…To address the lack of expressiveness difficulties and to adapt the ERP system to corporate business processes, extensive adjustments to the ERP system are recommended (Chakravorty et al, 2016;. ERP vendors should have more precise and divisional solutions that meet the demands of these businesses to meet their requirements and address the issue of ERP system organizational in-adaptation (Arachchi et al, 2019).…”
Section: Erp/organizational Misfitmentioning
confidence: 99%
See 1 more Smart Citation